Ministry of Education Curriculum Implementation Operational Guidelines - Trinidad and Tobago. Ministry of Education (Ministry of Education, Trinidad and Tobago, 2020)
This document contains general guidelines intended for implementation at both Primary and Secondary Level Schools in Trinidad and Tobago with respect to curriculum coverage and operations in Term I 2020/21, in the first instance.
Teaching and Learning Guidelines: Term I 2020/2021
Keywords: Curriculum implementation; Operational guidelines; Teaching and learning; Primary school; Secondary school; Trinidad and Tobago